2020
DOI: 10.1007/s10792-019-01262-x
|View full text |Cite
|
Sign up to set email alerts
|

Link of ocular pseudoexfoliation syndrome and vascular system changes: results from 10-year follow-up study

Abstract: Purpose To examine the 10-year incidence of the pseudoexfoliation syndrome (PEX) in adults in a population-based follow-up study, to determine its link with vascular diseases, and to identify possible risk factors of the PEX. Methods The baseline examination was performed in 2006 on a random sample of 1033 participants from Kaunas city (Lithuania) population. In 2016, a followup study of 686 participants who returned for the examination was conducted. The respondents filled out a questionnaire, an ophthalmolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
(56 reference statements)
0
18
0
2
Order By: Relevance
“…The only study that provides long-term follow-up information in PEX patients recently published is the ten-year patient follow-up study with 686 patients, which is conducted by Rumelaitiene et al In this study, it is demonstrated that PEX frequency increased from 10.3% to 34.2% at the end of 10 years and that it is associated with 1.5 times more ischemic heart disease and 1.6 times more ischemic heart disease and stroke in PEX patients. 18 The results of this study suggested that a more detailed cardiovascular evaluation of PEX patients might be needed. From this point of view, the subclinical myocardial dysfunction in strain echocardiography imaging correlated with the severity of coronary artery disease should be kept in mind.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The only study that provides long-term follow-up information in PEX patients recently published is the ten-year patient follow-up study with 686 patients, which is conducted by Rumelaitiene et al In this study, it is demonstrated that PEX frequency increased from 10.3% to 34.2% at the end of 10 years and that it is associated with 1.5 times more ischemic heart disease and 1.6 times more ischemic heart disease and stroke in PEX patients. 18 The results of this study suggested that a more detailed cardiovascular evaluation of PEX patients might be needed. From this point of view, the subclinical myocardial dysfunction in strain echocardiography imaging correlated with the severity of coronary artery disease should be kept in mind.…”
Section: Discussionmentioning
confidence: 87%
“…Although the results of these studies suggest that there might be a weak relationship between PEX and CAD, cardiovascular involvement may be due to accumulation in other cardiac tissues. The only study that provides long‐term follow‐up information in PEX patients recently published is the ten‐year patient follow‐up study with 686 patients, which is conducted by Rumelaitiene et al In this study, it is demonstrated that PEX frequency increased from 10.3% to 34.2% at the end of 10 years and that it is associated with 1.5 times more ischemic heart disease and 1.6 times more ischemic heart disease and stroke in PEX patients 18 . The results of this study suggested that a more detailed cardiovascular evaluation of PEX patients might be needed.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…An association between PEX and systemic diseases such as diabetes, ischemic heart disease, systemic hypertension, asthma, and rheumatoid arthritis has been discussed [7,8]. Manaviat et al investigated the association between PEX and diabetes.…”
Section: Discussionmentioning
confidence: 99%